The management of severe aortic stenosis during the COVID-19 pandemic: an observational study comparing TAVI and SAVR. (14th October 2021) - Akhtar, M; Shafi, A; Khanna, V; Mukhopadhyay, S; Patel, K; Ozkor, M; Baumbach, A; Mathur, A; Kennon, S; Awad, W; Mullen, M M
Abstract: Introduction: Outcomes and characteristics of patients with severe aortic stenosis (AS) treated during the COVID-19 pandemic is unknown. Methods: This was a single-centre observational study of patients undergoing AS treatment with transcatheter (TAVI) or surgical (SAVR) therapy during the first-wave of the UK COVID-19 pandemic compared to a control cohort undergoing treatment in 2019. Demographics, baseline echocardiogram, CT, procedural characteristics and outcome data were collated. The primary outcome was 30-day all-cause mortality. The secondary endpoint was duration of post-procedural hospitalisation. Results: 319 patients were recruited - 122 underwent intervention during the pandemic [73 TAVI; 49 SAVR] and 197 in 2019 [127 TAVI; 70 SAVR]. In 2020, TAVI patients had a higher Euroscore II (p<0.001) but there were no differences in procedural complications or mortality [p=0.16] compared to TAVI 2019 cases. Duration from TAVI to discharge was shorter in 2020 (p<0.001). SAVR 2020 patients had similar baseline profile [p=0.48], surgical characteristics, mortality (p=0.68) and duration from SAVR to discharge compared to those in 2019. During the pandemic, TAVI patients were older (p<0.001) and had a higher Euroscore II (p<0.001) than SAVR counterparts. TAVI patients had reduced 30-day mortality [0 (0%) vs 3 (6%); p=0.06] and were discharged more rapidly post-intervention than SAVR patients [median 1 [1] vs 7 [4] days; p<0.001) translating into shorter hospitalization (p<0.001). Conclusions: TAVI and SAVR can be safely delivered with predictable resource utilisation during a pandemic. Despite the TAVI cohort incorporating higher risk, older patients, outcomes were at least as good as SAVR with a shorter length of post-procedural hospitalisation. Funding Acknowledgement: Type of funding sources: None.